Kemiri Sunan Buds Induction (Reutealis trisperma (Blanco) Airy Shaw) For In Vitro in Ms Media with Different Concentrations of the Substance Growing Manager - Ningseh, Duwi Risti; Nursandi, Fatimah; Roeswitawati, Dyah (Universitas Muhammadiyah Malang, 2024)
Need oil fuel in Indonesia has increased. Oil production reached only 410,000 barrels per day while the needs of up to 1 million barrels per day. One plant is capable of producing biofuels is Pecan sunan. Vegetative reproduction has been hampered by the limited number of obtained so that necessary research in vitro. This research aims to know the concentration of the substance growing balance sitokinin (BA, TDZ and kinetin) and Auxin (NAA) in Pecan sunan buds induces on the MS medium. Experimental design used was Complete Random Design simple. The treatment is the composition of the basic MS medium with medium that is combined with the astringent balance grow NAA (0.5 mg/l), BA (1-3 mg/l), TDZ (0.2 mg/l) and kinetin (2 mg/l). The result of the observation form buds, but callus changes color and size kalus. Before and after color callus subculture of potentially forming buds is the A9 (MS + 0.5 mg/l NAA + 3 mg/l BA + 2 mg/l kinetin). While kalus response tends to be good on the A5 is 0 MS media (MS + 0.5 mg/l NAA + 2 mg/l BA + 0.2 mg/l TDZ) and G media is A2 (MS + 0.5 mg/l NAA + 2 mg/l BA).